Improving Third Grade Students’ Critical Thinking Skills Using Time Bar Media - Wahyu Purwaningsih; Ali Mustadi; Danuri Danuri (International Journal on Emerging Mathematics Education, 2021)
This study aims to improve the students’ critical thinking skills using time bar media in mathematics learning of Grade IIIA of SD Negeri 1 Kotagede – an elementary school in Yogyakarta, Indonesia. It used classroom action research design by Kemmis and McTaggart. The data were collected through observation, written tests, and interviews. The obtained data were analyzed using descriptive quantitative and qualitative techniques. The results showed that the use of time bar media in mathematics learning could improve students' critical thinking skills. The critical thinking skills covered: (1) providing simple explanations, (2) building basic skills, (3) concluding, (4) providing further explanations, and (5) arranging strategies and tactics. The increase in students' critical thinking skills was seen based on the test results in the pre-action (43%) which increased to 80% in the first cycle and increased to 90% in the second cycle.